2011
DOI: 10.3201/eid1701.101174
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Conditions and Human Listeriosis, England, 1999–2009

Abstract: The epidemiology of listeriosis in England and Wales changed during 2001–2008; more patients >60 years of age had bacteremia than in previous years. To investigate these changes, we calculated risk for listeriosis by concurrent condition for non–pregnancy-associated listeriosis cases reported to the national surveillance system in England during 1999–2009. Conditions occurring with L. monocytogenes infection were coded according to the International Classification of Diseases, 10th Revision, and compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
2
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 14 publications
3
66
2
5
Order By: Relevance
“…The incidence of listeriosis varies with countries and time. European countries have an increased incidence in recent years of 2 to 6 cases/million population (Mook et al 2011). No data about the comorbidity of listeriosis and malaria are available so far.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of listeriosis varies with countries and time. European countries have an increased incidence in recent years of 2 to 6 cases/million population (Mook et al 2011). No data about the comorbidity of listeriosis and malaria are available so far.…”
Section: Discussionmentioning
confidence: 99%
“…This includes not only pregnant women and the elderly, but those with underlying conditions. For example, Mook, O'Brien, and Gillespie (2011) found that many listeriosis patients in a 10-year study in England had kidney and liver disease, history of alcoholism, renal transplant, diabetes, systemic lupus erythematosus. Cancer patients accounted for more than one third of listeriosis cases, and high risks were observed for most cancer subgroups.…”
Section: Consumer Responsibilitymentioning
confidence: 99%
“…Cancer patients accounted for more than one third of listeriosis cases, and high risks were observed for most cancer subgroups. Because there is no appropriate food safety advice specifically for cancer patients in the UK, Mook et al (2011) suggests that the government put emphasis on this group to help prevent further cases.…”
Section: Consumer Responsibilitymentioning
confidence: 99%
“…Cancer patients also show increased susceptibility to L. monocytogenes (Table 3). In England and Wales in 1999-2009 cancer patients accounted for more than onethird of non-pregnancy-associated listeriosis cases (Mook et al, 2011). Two patients with oral cancer developed listeriosis after eating large quantities of soft cheese to counteract severe mouth soreness (Morritt et al, 2002).…”
Section: People With Pathological or Iatrogenic Immunosuppressionmentioning
confidence: 99%